Everyday Rituals in Contemporary Settings : The Semiotics of Space and Places of Consumption - Giannitrapani, Alice, (Brill Research Perspectives in Humanities and Social Sciences, 2025)
A boutique, a cruise ship, a museum and a hotel all have something in common. But what? They are all places of consumption-not just in the narrow economic sense, but also as part of a broader cultural, emotional, and symbolic phenomenon. Drawing on a semiotic approach, this book explores how designed environments from foodscapes to memorials convey meanings and guide everyday rituals, helping us to understand how space works as a language that structures practices, communicates values, and expresses identities. If you're curious about how places work, why they affect us, and what they say, this book gives you the tools to decode them.